Project-based Learning in The Relationship of Motivation and Critical Thinking to The Competence of Electrical Engineering Students - Isnur Haryudo, Subuh; Ekohariadi; Munoto; Anifah, Lilik; Achmad, Fendi (Journal of Engineering Education Transformations, 2022)
Project-based learning (PjBL) is a meaningful learning model in empowering and developing the skills of college students. PjBL will affect the motivation and critical thinking patterns of college students towards the achievement of 21st-century competencies. The purpose of this study was to determine the relationship between motivation and critical thinking on the competence of electrical through project-based learning. The research method uses a qualitative approach with an explanatory type. The research respondents were 302 final-year Electrical Engineering students from 5 universities with the competence of Electrical Installation Automation. The research instrument used a student response questionnaire type of measures of typical performance (MTP). The results of the statistical analysis test using SEM-PLS obtained a positive R-Square (indicator reliability) value of 0.961 or 96% having predictive relevance, meaning that motivation and critical thinking have a positive and significant impact on the competence of Electrical Engineering students.